Pathology of Silver Rasbora (Rasbora argyrotaenia) After Injection of Polyhhenol From Kappaphycus alvarezii - Kumalaningrum, Dwi Retna; Mauludia, Farida; Asyabil, Alin; Wahyudi, Diki; Amalya, Tria; Prayogi , M. Fahmi Dimas (JFMR-Journal of Fisheries and Marine Research, 2025)
Rasbora argyrotaenia is an endemic Indonesian freshwater fish with high economic value. However, its population has decreased due to overexploitation and environmental pollution. One of the sustainable aquaculture approaches that is being developed is the utilisation of natural bioactive compounds such as polyphenol from Kappaphycus alvarezii seaweed. This study aimed to evaluate the pathological impact of polyphenol extract injections from K. alvarezii at various doses on the liver of silver rasbora.  The test fish were given injections into their abdomens at doses of 5.4, 7.2, and 9.0 mg/kg body weight. Tannic acid was used as the positive control, and no injection was given as the negative control. Histopathological results revealed hepatocyte degeneration and necrosis, which worsened at a dose of 9.0 mg/kg, indicating oxidative stress as the primary mechanism of tissue damage. Water quality parameters during the study were within the optimal range for fish life. These findings suggest that while polyphenols have the potential to act as immunostimulants, their use at high doses may cause significant liver toxicity. Therefore, their utilisation in aquaculture must be carefully managed and based on optimal dosages.